Patrimoine, désenclavement et tourisme rural dans l’Anti-Atlas marocain - André Humbert (Belgeo)
Moroccan cultural toursim is an old custom; it dates back to the Protectorate era, from the 1920s. It first favored the so-called imperial cities before expanding to the south-east, in the Oriental Anti-Atlas. The Western Anti-Atlas yet endowed with a certain wealth of heritage, in a rural and agrarian environment, has not known, until now, the same craze, despite the proximity of Agadir, major tourist center. The article tries to explain this delay in the tourism development of this part of the Atlas chains and also presents examples of heritage sites and objects likely to attract tourists. As this part of the Atlas has only recently interested a few Moroccan or foreign geographers, this article is based on these few researches and especially on the numerous and punctual observations made, by the author, during the last two or three decades, until 1999.